2010
DOI: 10.3945/ajcn.2010.29363
|View full text |Cite
|
Sign up to set email alerts
|

Can gestational weight gain be modified by increasing physical activity and diet counseling? A meta-analysis of interventional trials

Abstract: Background: Excessive gestational weight gain (GWG) increases the risk of a number of adverse pregnancy outcomes and was recently identified as a potential risk factor for childhood obesity. It is therefore of interest whether GWG can be modified by an intervention combining dietary counseling and physical activity. Objective: The objective was to review published data on interventions to reduce GWG by modulating diet and physical activity during pregnancy. Design: We systematically reviewed 4 databases and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
183
2
10

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 204 publications
(198 citation statements)
references
References 39 publications
(99 reference statements)
3
183
2
10
Order By: Relevance
“…A meta-analysis of randomized controlled trials, focusing on diet and physical activity during pregnancy as intervention, showed that interventions may be effective to control weight gain during pregnancy (40). However, as maternal overweight and obesity are strongly associated with shortterm and long-term adverse consequences, future preventive strategies should also focus on prepregnancy overweight and obesity.…”
Section: Obesitymentioning
confidence: 99%
“…A meta-analysis of randomized controlled trials, focusing on diet and physical activity during pregnancy as intervention, showed that interventions may be effective to control weight gain during pregnancy (40). However, as maternal overweight and obesity are strongly associated with shortterm and long-term adverse consequences, future preventive strategies should also focus on prepregnancy overweight and obesity.…”
Section: Obesitymentioning
confidence: 99%
“…Interventions based on increasing physical activity (17,18); dietary advice (19); or by a combination of physical activity, supplementary weight monitoring, and nutritional counselling have been shown to be effective in reducing total GWG (20). A recent meta-analyses suggested that dietary measures might be most effective (21).…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle intervention studies also showed successful results with respect to the prevention of excessive GWG. Two reports using meta-analyses of intervention trials showed that exercise programs, combined with or without nutrition counselling, helps to limit GWG (Streuling et al, 2010a;Streuling et al, 2010b). Interventions that combined exercise and dietary counseling were found to be more successful in limiting GWG, with an average reduction of GWG of 1.2 kg (p=0.01) found in the intervention groups compared to the control groups (Streuling et al, 2010b).…”
Section: Maternal Physical Activity Is Associated With Preventing Excmentioning
confidence: 99%
“…Two reports using meta-analyses of intervention trials showed that exercise programs, combined with or without nutrition counselling, helps to limit GWG (Streuling et al, 2010a;Streuling et al, 2010b). Interventions that combined exercise and dietary counseling were found to be more successful in limiting GWG, with an average reduction of GWG of 1.2 kg (p=0.01) found in the intervention groups compared to the control groups (Streuling et al, 2010b). Three studies found significant lower GWG in the exercise plus nutrition intervention group compared with the control groups (Asbee et al, 2009;Claesson et al, 2008;Shirazian et al, 2010), 3 studies found a non significant trend in lower GWG in the intervention group compared with the control group (Gray-Donald et al, 2000;Guelinckx et al, 2010;Olson et al, 2004) and three found no significant results (Hui et www.intechopen.com al., 2006;Kinnunen et al, 2007;Polley et al, 2002).…”
Section: Maternal Physical Activity Is Associated With Preventing Excmentioning
confidence: 99%